FY2017 : Output Cost Estimates and Budget Outturn Paper. (Policy Papers; Policy Paper ;, 2017)
With continued efforts to maximize the use of available resources, the FY 17 outturn represents a small increase in spending within a largely flat budget envelope. Reallocations from lower priority areas and efficiency gains, along with flexibility provided by carry forward resources enabled the Fund to deliver on the initiatives and priorities in the Global Policy Agenda and Management's Key Goals. In terms of outputs, there was a small shift in spending from country and regional work to policy work. Within the former, spending moved from lending activities towards bilateral surveillance and capacity development. In terms of inputs, the structural budget was almost fully utilized. Highlights are presented followed by a discussion of the outputs and inputs. Details on capacity development are presented in the Annex.